Comunicação alternativa ampliada sob a ótica dos profissionais atuantes em cuidados paliativos no contexto hospitalar - Aguilera, Giovanna Barbosa (Universidade Federal de São Carlos, 2022)
Introduction: Communication is the main way for the relationship between patient, family and team, being an extremely important tool to ensure the patient's wishes, sustain their hope and reduce the fears linked to the experience of the illness process. Faced with situations of temporary or permanent impediments to the patient's verbal expressions, it is necessary to offer an alternative way to perform the communicative function. Objectives: This study aimed to verify the use of alternative and expanded communication by professionals working in palliative care in the hospital context with the adult and elderly population. Methodology: This is a cross-sectional, exploratory study, involving a field survey with a quantitative-qualitative approach. Data collection took place through an online questionnaire, with data analyzed using simple descriptive statistics and content analysis. Results: Fifteen health professionals participated in this research, who consensually expressed the level of maximum importance attributed to the communication skill in palliative care, a factor supported by three central ideas: basis of palliative practice, path to singular therapeutic planning and active participation of the patient in treatment and a tool for multidimensional assessment of suffering. However, in the face of clinical conditions in which the patient's communication is altered, some professionals mentioned a lack of preparation to provide communication through alternative resources. When using resources for expanded alternative communication, it was noticed that the approach is limited, focused especially on the identification of symptoms and basic needs, with reduced exploration of multidimensional aspects. Conclusion: It was found that there is clarity among the participants about the importance of communication in the care process and that the deprivation of spaces for expression and exchanges constitutes a potential element of suffering. In view of this understanding, part of the professionals mentioned strategies used within poorly systematized actions, a factor associated with low education on assistive resources and the absence of a multiprofessional hospital team to support such implementations.
Alternative communication from the perspective of professionals working in palliative care in the hospital context
Keywords: Comunicação em saúde; Sistemas de comunicação alternativos e aumentativos; Cuidados paliativos; Assistência hospitalar; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL